Calcium pyrophosphate deposition disease: historical overview and potential gaps - Pineda, Carlos; Sandoval, Hugo; Pérez-Neri, Iván; Soto-Fajardo, Carina; Carranza-Enríquez, Fabián (Frontiers in Medicine, 2024)
CPPD disease can affect patients’ quality of life through its various clinical presentations. This mini-review discusses the evolution of CPPD from its discovery to current knowledge of its pathogenesis, genetic associations, diagnostics, and treatment options. Despite extensive research, the exact mechanisms of CPPD are not well understood, and there is a notable lack of knowledge about psychosocial impacts and patient experiences. This study aims to present a CPPD Disease Timeline identifying gaps in current knowledge and potential directions for future research. These findings contribute to a broader understanding of CPPD disease and emphasize the importance of continued research and innovation in this field.